Impact of in-feed versus in-water chlortetracycline and tiamulin administrations on fecal prevalence and antimicrobial susceptibilities of Campylobacter and Salmonella in a population of nursery piglets - Ishengoma, Victor Landelinus (Kansas State University, 2021)
Antimicrobial resistance (AMR) in bacteria is a growing public health concern in the US and around the world threatening the continual use of antimicrobials. Antimicrobial resistant Campylobacter and Salmonella are listed as serious level threats to the public health by the Centers for Disease Control and Prevention. Campylobacter and Salmonella are common foodborne pathogens that reside in the gut of pigs and are shed in feces with the potential to be transmitted to humans. In pigs, oral route, either in-feed or in-water, is by far the most common route of administration of antimicrobials. Because the distribution of the antibiotic in the gut and the dosages are different, the impact of in-feed vs. in-water administration of antibiotics on the development of AMR is likely to be different. Therefore, a study was conducted to compare in-feed vs. in-water administrations of chlortetracycline (CTC) and or tiamulin on fecal prevalence and AMR profiles of Campylobacter and Salmonella in nursery piglets. A total of 1,296 weaned piglets, allocated into 48 pens (27 piglets per pen), were assigned randomly to six treatment groups: Control (no antibiotic), in-feed CTC, in-water CTC, in-feed tiamulin, in-water tiamulin, or in-feed CTC and tiamulin. Fecal samples were collected randomly from 5 piglets from each pen during pre-treatment (days -7, 0), treatment (days 7, 14) and post-treatment (days 21, 28) phases. Bacterial isolations and species identifications were done by culture and PCR, respectively. The microbroth dilution method with Sensititre™ plates were used to determine antimicrobial susceptibility and resistance of Campylobacter and Salmonella strains. The results on resistance were interpreted based on the Clinical and Laboratory Standards Institute (CLSI) guidelines for Salmonella and the European Committee on Antimicrobial Susceptibility Testing (EUCAST) epidemiological cutoff values for Campylobacter. Whole genome sequencing (WGS) of Campylobacter and Salmonella isolates was done on an Illumina HiSeq platform. Overall prevalence of Campylobacter and Salmonella were 18.2% (262/1,440) and 3.0% (43/1,440) respectively. Speciation of Campylobacter isolates by PCR indicated C. hyointestinalis (17.9%; 258/1,440) and C. coli (0.3%; 4/1,440), while WGS indicated that all the Salmonella strains were serovar Typhimurium. Campylobacter isolates were resistant to tetracycline (98.5%), ciprofloxacin (89.3%), and nalidixic acid (60.3%). Salmonella isolates were susceptible to azithromycin and totally resistant (100%) to ampicillin, streptomycin, sulfisoxazole, tiamulin, and tetracycline. Also, WGS revealed a high correlation of phenotypic and genotypic AMR in both Campylobacter and Salmonella. Most of the Campylobacter and Salmonella isolates were multidrug resistant. Neither antibiotic nor the route of administration had an effect (P > 0.05) on the occurrence of resistant Salmonella or Campylobacter in the feces of piglets.
Keywords: Campylobacter; Salmonella; Antimicrobial; Antimicrobial resistance; In-feed; In-water